2022
DOI: 10.20473/imhsj.v6i2.2022.138-149
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy Diet Practices and Anemia in Young Women

Abstract: Background: Adolescent anemia needs to be the focus of attention because anemia in young women can have an impact on health during pregnancy and childbirth. Meanwhile, many young women practice unhealthy diet for various reasons. This study was conducted to determine the relationship between unhealthy diet practices and anemia status in female high school students in Malang. Method: This study used an observational analytic design with a cross-sectional approach. The research was conducted in 5 public high sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The Chi-Square statistical test showed that the p-value is 0.016 (p≤0.05), meaning that there was a significant relationship between iron intake and the incidence of Anemia with an OR of 7.929 (CI = 6.202 -9.655). So, it can be concluded that female students with insufficient Iron intake had a 7.929 times greater risk of experiencing Anemia compared to female students who have sufficient Iron intake 14 .…”
Section: Bivariate Analysis Resultsmentioning
confidence: 97%
“…The Chi-Square statistical test showed that the p-value is 0.016 (p≤0.05), meaning that there was a significant relationship between iron intake and the incidence of Anemia with an OR of 7.929 (CI = 6.202 -9.655). So, it can be concluded that female students with insufficient Iron intake had a 7.929 times greater risk of experiencing Anemia compared to female students who have sufficient Iron intake 14 .…”
Section: Bivariate Analysis Resultsmentioning
confidence: 97%
“…Anemia in adolescent girls can be caused by various factors, such as menstrual bleeding (Turner, Parsi, & Badireddy, 2023;Chai, Huang, Rakočević, & Chung, 2021), inadequate intake of iron-rich and protein-rich foods (Sari, Judistiani, Herawati, Dhamayanti, & Hilmanto, 2022), improper diets (Setyaningsih, Mansur, & Naimah, 2022), and non-compliance with iron supplement intake (Humayrah & Putri, 2023;Sirupa, Wantania, & Suparman, 2016). These factors can negatively impact cognitive function, leading to fatigue, decreased concentration, and academic underperformance.…”
Section: Introductionmentioning
confidence: 99%